Rebel sisters - Onyebuchi, Tochi (Razorbill, 2020)
Living a comfortable life in the Space Colonies, Ify, now nineteen and a medical administrator, must return to wartorn Nigeria, where she last saw her sister, to investigate why young refugees from that nation are carrying a deadly virus.